A study to evaluate the efficacy of combined prostaglandins and vaginal estradiol compared to prostaglandin alone in labor induction - B., Anjana; Sheikh, Saniya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Induction of labor (IOL) is a process where labor is initiated artificially before its spontaneous onset for the delivery of feto placental unit by mechanical or pharmacologic methods. Methods: The present Hospital based prospective randomized comparative study was conducted in the department of obstetrics and gynecology, KLES Dr. Prabhakar Kore Charitable Hospital, Belagavi during the period of January 2015 to December 2015.The selected women were randomized into two groups by simple randomization using an opaque sealed envelope, into either without vaginal estradiol Group A: Group PGE2 - Prostaglandin E2 gel intracervical alone group or Group B: PGE2 + E (Estradiol) - combined Prostaglandin E2 gel intracervical and 50 µg of estradiol tablet intravaginal group. Results: In the present study 65% of the women in group PGE2 required three doses of prostaglandins compared to 23.33% in group PGE2 and estradiol for the cervix to become favorable. In this study there is significantly longer mean interval time noted for induction to cervical ripening (12.88±4.91 versus 8.92±5.07; p <0.001), induction to active labor (16.97±4.93 versus 11.02±4.72; p <0.001) and induction to delivery time (21.97±3.83 versus 13.14±4.98; p <0.001) in group PGE2 compared to combined PGE2 and estradiol group. Conclusions: Thus, vaginal estradiol along with prostaglandins has the potential in cervical ripening and induce labor and in an efficacious way. There is beneficial fetal outcome when combined vaginal estradiol along with intracervical prostaglandin E2 was used.